Performance Evaluation of Chestnut Nano Particles on Tensile, Impact, Vickers Hardness of Polyester/Glass Fiber Composite - Hussein, Samah M.; Rasheed, Zaynab N. (Iraqi Journal of Science, 2023)
In this study, an industrial source) E-Glass fiber) and a natural source (chestnut filler) were combined to improve the properties of polyesters. Hand-layup technique was applied in this work. Polyester (UPE) were reinforced with E-glass fibers, then reinforced with nano chestnut particles. All composites were prepared with (10% wt.) of E-glass for all prepared sheet and this ratio applied for Nano chestnut composite to preparing nano hybrid composites, Nano chestnut particles were used to reinforce E-glass/UPE composites with weight ratio (3%, 6% and 9% wt.). The evaluated mechanical performances for E-glass/NCSP polyester composite were tensile strength, impact strength and hardness. The higher ultimate tensile strength, Young’s modulus and impact strength was appeared for the E-glass/UPE composite with 3%wt nano chestnut filler only. While the composites with 6% and 9% wt. showed failure in these properties. Hardness property was high with the three percentage addition of nano powder of chestnut.